2017
DOI: 10.1007/s12262-016-1581-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection and Prognostic Analysis of 142 Cases of Hilar Cholangiocarcinoma

Abstract: Surgical resection for hilar cholangiocarcinoma is the only curative option, but low resectability rate and poor survival outcomes remain a challenge. This study was to assess the surgical resection for hilar cholangiocarcinoma and analyze the prognostic factors influencing postoperative survival. One hundred forty-two patients with hilar cholangiocarcinoma who underwent surgical resection between January 2006 and December 2014 were analyzed retrospectively based on clinicopathological and demographic data. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several previous studies revealed that the prognosis of HCCA resection is affected by multiple factors, including age at time of surgery, preoperative biliary drainage, presence or absence of radical resection, resection margin status, tumor markers, pathological type, lymph node metastasis, and postoperative adjuvant therapy [23][24][25][26][27] . The present study combined clinical practice parameters and Cox univariate and multivariate regression analysis to screen the effect of these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies revealed that the prognosis of HCCA resection is affected by multiple factors, including age at time of surgery, preoperative biliary drainage, presence or absence of radical resection, resection margin status, tumor markers, pathological type, lymph node metastasis, and postoperative adjuvant therapy [23][24][25][26][27] . The present study combined clinical practice parameters and Cox univariate and multivariate regression analysis to screen the effect of these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the only potentially curative option for CCA; however, the five-year survival rate after resection ranges from 25% to 40% [3]. Factors associated with low survival rates include vascular invasion, organ invasion, and residual tumor lesions after resection [4][5][6].…”
Section: Introductionmentioning
confidence: 99%